Software Engineering for Resilient Systems Fourth International Workshop, SERENE 2012, Pisa, Italy, September 27-28, 2012, Proceedings - Avgeriou, Paris (Programming and Software Engineering, 2012)
This book constitutes the refereed proceedings of the Fourth International Workshop on Software Engineering for Resilient Systems, SERENE 2012, held in Pisa, Italy, in September 2012. The 12 revised full papers were carefully reviewed and selected from numerous submissions. The papers address all aspects of fault tolerance and exception handling, safety modeling, supporting evolution, resilience in service-oriented computing, and applying formal methods in case studies.